Controllable Synthesis of 2D Perovskite on Different Substrates and Its Application as Photodetector - Yunzhou Xue (Nanomaterials, 2018)
Perovskites have recently attracted intense interests for optoelectronic devices application due to their excellent photovoltaic and photoelectric properties. The performance of perovskite-based devices highly depends on the perovskite material properties. However, the widely used spin-coating method can only prepare polycrystalline perovskite and physical vapor deposition (PVD) method requires a higher melting point (>350 °C) substrate due to the high growth temperature, which is not suitable for low melting point substrates, especially for flexible substrates. Here, we present the controlled synthesis of high quality two-dimensional (2D) perovskite platelets on random substrates, including SiO2/Si, Si, mica, glass and flexible polydimethylsiloxane (PDMS) substrates, and our method is applicable to any substrate as long as its melting point is higher than 100 °C. We found that the photoluminescence (PL) characteristics of perovskite depend strongly on the platelets thickness, namely, thicker perovskite platelet has higher PL wavelength and stronger intensity, and thinner perovskite exhibits opposite results. Moreover, photodetectors based on the as-produced perovskite platelets show excellent photoelectric performance with a high photoresponsivity of 8.3 A·W−1, a high on/off ratio of ~103, and a small rise and decay time of 30 and 50 ms, respectively. Our approach in this work provides a feasible way for making 2D perovskite platelets for wide optoelectronic applications.